2020
DOI: 10.1002/jwmg.21989
|View full text |Cite
|
Sign up to set email alerts
|

Hatch Success and Recruitment Patterns of the Bog Turtle

Abstract: Researchers suggest that several bog turtle (Glyptemys muhlenbergii) populations in North Carolina, USA, are in decline and have few remaining individuals and low annual survival probability. Most populations are dominated by older adults with few juveniles encountered; however, the proportion of juveniles encountered in 2 populations is higher. It is unknown why the juvenile:adult ratio varies among populations. We conducted a nest monitoring study in 2016 and 2017 to test the hypothesis that sites with fewer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Of the five bog turtle populations modeled, we found only two that exhibited stability or growth when incorporating site‐specific vital rates (Sites A and B). As evidenced by capture data, recruitment has been continuous for at least a decade at sites A and B, and successful recruitment likely results from lower nest predation, moderate incubation temperatures (Knoerr et al ., 2021), and high juvenile survival (Tutterow et al ., 2017). Our results for Sites A and B demonstrate how population stability can be maintained even when adult survival declines (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the five bog turtle populations modeled, we found only two that exhibited stability or growth when incorporating site‐specific vital rates (Sites A and B). As evidenced by capture data, recruitment has been continuous for at least a decade at sites A and B, and successful recruitment likely results from lower nest predation, moderate incubation temperatures (Knoerr et al ., 2021), and high juvenile survival (Tutterow et al ., 2017). Our results for Sites A and B demonstrate how population stability can be maintained even when adult survival declines (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Data collected in 1996–2017 indicated that juveniles were highly represented in both populations (observed juvenile fractions > 0.4) and juvenile survival (0.81 and 0.77, respectively) was an average of 38% higher in these populations than in Sites D and E (values derived from Tutterow et al ., 2017 and more recently collected data; see ‘Materials and methods’ section). Sites A and B experienced successful recruitment in each of the last 10 years, determined by counting growth rings over the 2016–2017 field seasons, and egg survival rates were high in 2016 and 2017 (62 of 120 eggs survived to yield a 0.52 pooled average egg hatch rate; Knoerr, Graeter & Barrett (2021)).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations